Supporting Muslim undergraduate medical students through medical school: lessons from a novel, student-led case-based learning intervention - Mohammed, Zain; Ba, Hafsah; Nasim, Linta; Reid, Emily Roisin (Frontiers in Medicine, 2025)
IntroductionMuslim medical students in the UK face discrimination, microaggressions, and inadequate institutional support, affecting their well-being, academic experience and outcomes. Using Case-Based Learning (CBL) as a pedagogical framework, a novel student-led teaching intervention was created and delivered to small groups of faculty and students, with the aim of enhancing awareness, promoting inclusivity, and supporting educators of these issues.MethodsThis CBL intervention was designed and led by Muslim medical student facilitators with subject expertise and previous experience in implementing curricular interventions. Scenarios based on real-life student experiences explored authentic challenges Muslim students face during their medical studies. Data were gathered to assess the effectiveness of the teaching innovation against its aims in the following formats: (1) in-session participant feedback, (2) transcriptions of the in-session discussions which demonstrated participant learning gain, and (3) notes from the post-session facilitator team reflections. These data were thematically analyzed using Braun and Clarke's six-point framework, with individuals coding the data individually and collectively across three meetings to refine and agree upon the themes.ResultsFive key themes of insights emerged from the data: Staff and Student cultural literacy relating to Islam, Facilities and Environment, Curriculum, Policy and Processes, Islamophobia and discrimination. The in-session discussions evidenced that participants had increased their cultural literacy and awareness of Muslim students' needs and identified practical solutions, including inclusive scheduling, making appropriate prayer facilities available to enable equitable educational attainment, providing clear clinical attire guidelines, and providing robust reporting mechanisms. The facilitators reflected that the students-as-experts aspect of the intervention equalized the usual faculty-student power dynamics. This promoted a sense of partnership that enabled participants in the sessions to take ownership of their own learning.DiscussionCBL presented a valuable format for student-faculty discussions to promote cultural competence and equity in medical education. Variability in assumed knowledge and cultural literacy posed challenges, reinforcing the need for broader implementation of Equity, Diversity and Inclusivity (EDI) training and enhanced institutional support networks to develop cultural literacy further.ConclusionThis student-led CBL educational innovation brokered a dialogue between students and faculty around solutions to the challenges faced by Muslim medical students. Given its success, student-led staff training could be expanded to address challenges faced by other minority groups, ensuring a more equitable and culturally competent learning environment.